УЛС ТӨРИЙН ИНСТИТУТ БА ОЛОН НИЙТИЙН ИТГЭЛ: ХАРЬЦУУЛСАН СУДАЛГАА - Ж.ТӨРТОГТОХ; Ч.Өлзийсайхан; Б.Эрдэнэдалай (Politology, 2023)
In western and some other advanced democratic systems, public trust in government has been declining since the 1960s. A large body of social science literature now supports this conclusion, generally focusing on one of two areas. In our research these are also considered as one of basic parts of methodology. The first group of studies suggests that public trust in govemment is a function of economic factors, social conditions such as crime and poverty, and political factors including scandals and job performance evaluations of elected officials and government institutions. A second line of research has found that trust in government helps to explain other political attitudes and behaviors. For example, declining levels of trust affect public evaluations of government, and vote intentions. Moreover, we should note that most of those research conducted by international scholars and research centers are mainly concerned on public trust or confidence issues on government and government institutions. Therefore, one of our research peculiarities is to cover not only govenment institutions but also other political institutions and we gave importance to comparative research and making integrated analyze on public confidence in those political institutions.